Potential and limitations of computed tomography images as predictors of the outcome of ischemic stroke events: a review - Oliveira, Gonçalo; Fonseca, Ana Catarina; Ferro, José M.; Oliveira, Arlindo L. (Frontiers in Stroke, 2023)
The prediction of functional outcome after a stroke remains a relevant, open problem. In this article, we present a systematic review of approaches that have been proposed to predict the most likely functional outcome of ischemic stroke patients, as measured by the modified Rankin scale. Different methods use a variety of clinical information and features extracted from brain computed tomography (CT) scans, usually obtained at the time of hospital admission. Most studies have concluded that CT data contains useful information, but the use of this information by models does not always translate into statistically significant improvements in the quality of the predictions.